Computer simulation of the mat formation of bamboo scrimber composites. (October 2021) - Pineda, Hugo; Hu, Yu'an; Semple, Kate; Chen, Meiling; Dai, Chunping
Abstract: Bamboo scrimber, including 'bamboo fibre composite' (BFC), is an engineered bamboo composite made by forming and consolidating resin-coated parallel bamboo bundles. The composite panel density is above 1000 kg/m 3, and exhibits variability arising from variations in culm bundle geometry and manual mat formation process. Based on object collision physics, this paper presents a novel computer simulation model for BFC mat formation in terms of bamboo bundle spatial arrangement and horizontal density distribution. The model was calibrated and validated using experimental data of commercial panels. While animating bundle deposition and 3D density distribution, the model also predicts the density variability (standard deviation, σρ ) in BFC panels. Parametric analyses using the model showed that bundle and panel thickness, bundle width and width taper have significant effects on σρ and hence the composite uniformity. This model provides a simulation platform for further analyses of mat consolidation and element orientation for bamboo and wood composites.